A rapid and facile preparation of novel macroporous silicone-based cryogels via photo-induced thiol-ene click chemistry - Ozmen, Mehmet Murat; Fu, Qiang; Kim, Jinguk; Qiao, Greg G. (ROYAL SOC CHEMISTRY, 2015)
Novel poly(dimethylsiloxane) based macroporous gels (cryogels) were prepared via a simple and rapid photo-induced thiol-ene click reaction at low temperatures. The cryogels formed were able to float on a water surface and selectively remove oils or organic solvents with excellent recyclability.
Keywords: OIL; RUBBER; REMOVAL; GELS; POLYDIMETHYLSILOXANE; POLYISOBUTYLENE; ABSORPTION; SEPARATION; SORBENTS; SPONGES; Chemistry